EFFECT OF TWO DIFFERENT PERMEABLE CRYOPROTECTANTS ON FREEZABILITY OF EXOTIC STALLION AND JACK SEMEN - TALLURI, T R; RAVI, S K; SINGH, C; LEGHA, R A; MEHTA, s c; PRAKASH, V; TRIPATHI, B N (The Indian Journal of Animal Reproduction, 2022)
Semen was collected from the exotic stallions and exotic jacks (n=5 each) using an artificial vagina. The fresh semen was treated with primary extender and centrifuged to remove seminal plasma. Sperm pellet obtained after centrifugation was equally divided to receive secondary extender containing same amount (5%) of different permeable cryoprotectants, either glycerol (Gly) or dimethyl formamide (DMF) before submitting for cryopreservation. Various sperm parameters were assessed at pre-freeze and post-thaw stage which revealed differences (p<0.05) in motility, liveability, plasma membrane integrity and acrosome integrity of stallion as well as Jack semen cryopreserved with DMF or Gly. A variation (p<0.05) existed between individual stallions and jacks extended either with DMF or Gly. In brief, cryoprotectant DMF for stallion and Gly for jack semen were suitable for retaining the plasma and acrosome integrity of spermatozoa.